(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The principle of this paper is to investigate maintenance and production problems in the cement factory in Libya with particular emphasis on Total Productive Maintenance (TPM). The paper presents the use of case study approach of production data and history, field visits. There is no clear TPM strategy and it has been also found that the lack of training and personal development is the main cause of this problem. In addition, employees are found not to be motivated as a result of the lack of poor management strategy and reward structure. Based on the findings, a new framework for TPM has been developed. This TPM strategy could be implemented in other Libyan factories as a result of the potential similarities in the cultural and environmental aspects. The comparative analysis is developed into a model for international strategy design and implementation. The paper highlights limitation is the cement factories in Libya in relation to TPM and production strategies. The importance of adopting a realistic strategy and framework by managers is discussed. This work is developed as collaboration between Academia and Libyan Cement industry for solving productivity problems and develop a strategic framework of TPM for improving the Libyan industry.